2007
DOI: 10.1021/nl070187t
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Phase Transition of Supported Gold Nanoparticles

Abstract: A thermal phase transition has been resolved in gold nanoparticles supported on a surface. By use of asynchronous optical sampling with coupled femtosecond oscillators, the Lamb vibrational modes could be resolved as a function of annealing temperature. At a temperature of 104°C the damping rate and phase changes abruptly, indicating a structural transition in the particle, which is explained as the onset of surface melting.Metallic nanoparticles are in the focus of fundamental and applied research. They show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 43 publications
6
82
0
Order By: Relevance
“…10(c) is consistent with the morphological properties of co-existing solid-liquid melts predicted for small particles through theoretical studies [40]. A similar thermal phase transition has been reported elsewhere through pump-probe vibration optical spectroscopy [45], albeit for significantly larger gold particles where the onset of surface melting was observed at 104 1C. Our experimental observations show that small particles ca.…”
Section: Surface Structures At Elevated Temperaturessupporting
confidence: 90%
“…10(c) is consistent with the morphological properties of co-existing solid-liquid melts predicted for small particles through theoretical studies [40]. A similar thermal phase transition has been reported elsewhere through pump-probe vibration optical spectroscopy [45], albeit for significantly larger gold particles where the onset of surface melting was observed at 104 1C. Our experimental observations show that small particles ca.…”
Section: Surface Structures At Elevated Temperaturessupporting
confidence: 90%
“…For non-spherical nanoparticles, a shape transformation into nanospheres 3 can be observed as the nanoparticle reduces its surface energy due to the applied heat. The melting of both spherical and rod-shaped gold nanoparticles can be interpreted in terms of surface melting [22][23][24][25], whereby there is a small difference in the melting temperatures for the different facets [26][27][28]. For gold nanorods the surface melting is accompanied by the transformation into nanospheres, which is explained by Insawa et al in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ruan et al, 22 have experimentally observed the reversible surface premelting of Au NPs ͑2-20 nm͒ under femtosecond laser irradiation. Experimental observations of surface premelting in 61.5 nm Au NPs were reported by Plech et al 23 If the existing models state that NPs larger than 20 nm cannot melt, this does not imply that they cannot be heated up. The corresponding temperature increase will depend on the NP size, i.e., the larger the NP the less it will heat up.…”
mentioning
confidence: 95%